Salt inhibition on anaerobic treatment of high salinity wastewater by upflow anaerobic sludge blanket (UASB) reactor - Aslan, Sibel; Sekerdag, Nusret (Taylor & Francis Inc, 2016)
The adverse effects of salt concentration on anaerobic treatment of synthetic high salinity wastewater were investigated using four lab-scale upflow anaerobic sludge blanket reactors at different salt (NaCl) concentrations. The reactors were inoculated with granular sludge previously not adapted to salinity, and they were fed with synthetic wastewater containing the salt concentrations of 0, 10, 25, and 50gL(-1) NaCl. Hydraulic retention time and organic loading rate were kept constant at 1d and 2kg chemical oxygen demand (COD) m(-3)d(-1), respectively. Salt inhibition on the COD removal rate and efficiency, methane production were determined. COD removal rate and efficiency significantly decreased when the salt concentration in the feed increased to 50gL(-1) from 0. The maximum COD removal was obtained at salt concentration of 10gL(-1).
Keywords: Anaerobic treatment; UASB; High salinity; NaCl; Inhibition